The Arm’s Length Standard in the International Tax Regime: Methods, Problems and Proposals - Buíssa, Leonardo; Bevilacqua, Lucas (Revista de Direito Tributário Internacional Atual, 2018)
This essay depicts the arm’s length consolidation as an international standard, the issues involving its implementation and solution propositions. For such, the study begins from the premise that there is an international tax regime as part of the international law and that transfer pricing, along with the arm’s length standard, displays a manifested example of this thesis. It is noted, through the undertaken historical overview, the international adoption of such standard. Strengthening the idea, transfer pricing methods pertained to the arm’s length principle are scrutinized, firstly the so-called traditional transaction methods, emphasizing comparability and secondly the transactional profit methods, in which the comparison between controlled transactions is still present, though flexibly. Furthermore, the existence of conceptual and practical problems surrounding the standard’s implementation are identified, especially the lack of ideal comparables. Finally, the essay presents solution propositions. Some within the standard, through the adoption of new transfer pricing methods and others apart from the arm’s length, indicating inclusively, its clash.